Especies de dinoflagelados del género Gambierdiscus (Dinophyceae) del Mar Caribe mexicano - Hernández-Becerril, D. U. (2004)
Some dinoflagellates with benthic habits are related to ciguatera intoxication by fish consumption, especially in tropical areas. In the Mexican Caribbean, ciguatera is relatively common, but only one paper seems to have been published on the subject, and there are very few publicactions on phytoplankton and benthic microalgae. Material collected along the coast of the State of Quintana Roo with phytoplankton net (54 mm) and directly from sediment and epiphytes of macroscopic plants, was searched for toxic and other associated dinoflagellates. Samples were studied by light and scanning electron microscopy. Morphological characters were useful for species identification, but eventually physiological, ecological and molecular characters could also be used. Three species of Gambierdiscus, related to the production of ciguatera toxins, were identified: G. belizeanus, G. toxicus and G. yasumotoi. They are distributed in shallow coastal areas, including coastal lagoons.